4x^2 - 1
Multiplying binomials of the form (a + b)(a - b) is quite easy, because the result is a^2 - b^2. In this case, a is 2x and b is 1. a^2 - b^2 = 4x^2 - 1
2007-06-07 03:39:04
·
answer #1
·
answered by DavidK93 7
·
0⤊
0⤋
Two things to know:
1.) F.O.I.L.
First = 2X*2X = 4X^2
Outside = 2X*(-)1 = -2X
Inside = 2X*1 = 2X
Last = 1*(-)1 = -1
add them all up and you get : 4X^2 - 1
2.) second order quadratic square:
a^2 - b^2 = (a + b)*(a - b)
The proof is F.O.I.L. and the thing to watch out for is two squared terms subtracted from each other.
2007-06-07 10:47:46
·
answer #2
·
answered by Roger S 7
·
0⤊
0⤋
(2x + 1) (2x - 1) = 4x^2 - 2x + 2x -1 = 4x^2 - 1 ( the x terms cancel out)
2007-06-07 10:49:12
·
answer #3
·
answered by Swamy 7
·
0⤊
0⤋
Well it depends on what the variable x means. For example, if 3 exuals x then the equation would be (2x3+1) x (2x3-1)
The answer to the first one is 7 and the answer to the second one is 5, so you do 7x5, which equals 35. Hope this helped!
2007-06-07 10:42:03
·
answer #4
·
answered by Sweet_Girl_32 2
·
0⤊
0⤋
( 2x+1 )( 2x-1)
We solve this by 2x ( 2x-1) + 1 ( 2x-1)
= 4x.x - 2x + 2x -1
= 4x.x -1 .
Actually you have to square both terms and put a minus sign between them.
2007-06-07 10:42:42
·
answer #5
·
answered by Sakaratmak_vicharsarani 2
·
0⤊
0⤋
use the form (a+b)(a-b) = a^2 + b^2
this gives (2x+1)(2x-1) = 4x^2 -1
2007-06-07 10:40:43
·
answer #6
·
answered by Vipin A 3
·
0⤊
0⤋
4x^2-2x+2x-1
4x^2-1
2007-06-07 10:41:59
·
answer #7
·
answered by Raziel Lives 4
·
0⤊
0⤋
(a+b)(a-b)=a^2-b^2
(2x+1)(2x-1)=(2x)^2-1^2
=4x^2-1
2007-06-07 10:51:21
·
answer #8
·
answered by cidyah 7
·
0⤊
0⤋
what is to be solved
2007-06-07 10:39:11
·
answer #9
·
answered by topsyk 3
·
1⤊
1⤋